Solving Child Crimes Through Restorative Justice and Diversion from Legal Sociological Aspects - Ayu Ningtias; Muhammad Aini (Riviera Publishing, 2026)
Since the 19th century, children have been objects of scientific study, yet legal responses to children in conflict with the law often prioritize punishment over protection. This research aims to analyze the application of restorative justice and diversion in resolving child crimes from the perspective of legal sociology. The study employed normative legal research using primary legal materials (laws and regulations) and secondary legal materials (legal literature, journal articles, and research reports), analyzed descriptively-analytically. The findings reveal that although Indonesian Law No. 11 of 2012 on the Child Criminal Justice System mandates diversion for children aged 12-18 years, its implementation faces obstacles due to a lack of understanding among law enforcement officials, societal pressure for retribution, and exceptions for serious crimes (punishable by over 7 years). Restorative justice, as developed by UNICEF, offers a recovery-oriented approach involving victims, perpetrators, and the community. The sociological perspective demonstrates that law is not merely a normative system but is embedded in social values, norms, and power relations. The practical implication is the need for capacity building for police, prosecutors, and judges, as well as community-based mediation programs to prioritize the best interests of the child.